Impact of Higher Education on Employment of Disadvantaged Groups: A Comparative Study between Türkiye and the EU - Selen Kabaca Çiçek; Osman Murat Çetin (Üniversite Araştırmaları Dergisi)
Within the scope of harmonization processes with the European Union (EU) legislation, increasing employment, improving working and living conditions, developing human resources for a sustainable employment structure, and social exclusion are among the fundamental issues covered by Chapter 19 on Social Policy and Employment. This study examines the employment policies and practices toward disadvantaged groups in Türkiye and the EU, and also highlights the impact of the variations in the definition of the concept of disadvantage across countries on the design and implementation of these policies. The study recognizes that the common definition of disadvantaged groups refers to individuals with disabilities, ex-convicts, women, and immigrants, and proposes to expand this definition to include those who are disadvantaged or become disadvantaged over time due to barriers to labour market access.